Maternal health literacy as an effort to reduce maternal mortality - Nursanti, Siti; Utamidewi, Wahyu; Tayo, Yanti; Nurhasanah, Hanna (Faculty of Communications Science, Dr. Soetomo University, 2021)
The Karawang Regency's progress in reducing maternal mortality through an expanding (EMAS) program does not inherently reduce maternal mortality. The change in the incidence of postpartum mother mortality has led the Government of the Karawang Regency to a breakthrough by implementing an appreciation of the level of mothers’ comprehension during the postpartum period between fathers. This research investigated the extent of the father's communication process in Kelas Bapak (Lit: Father Class) to improve the father's awareness of maternal health over the postpartum. This study employs descriptive qualitative methods of research. The study results found that Kelas Bapak inspired families to treat maternal health at the Regional General Hospital of Karawang Regency during the postpartum period. This study concludes that one of the causes of a father's lack of understanding about his mother is that his mother's health is unconcerned during the postpartum period.